Does job search assistance reduce unemployment? Experimental evidence on displacement effects and mechanisms - Maria Cheung; Johan Egebark; Anders Forslund; Lisa Laun; Magnus Rödin; Johan Vikström (Research Institute of Industrial Economics (IFN), 2019)
This paper uses a large-scale two-level randomized experiment to study direct and displacement effects of job search assistance. Our findings show that the assistance reduces unemployment among the treated, but also creates substantial displacement leading to higher unemployment for the non-treated. By using detailed information on caseworker and job seeker behavior we show that vacancy referrals passed on from caseworkers to job seekers is the driving mechanism behind the positive direct effect. We also examine explanations for the displacement effect and show that displacement is not due to constrained resources, but arises in the labor market. A comparison between different meeting formats suggests that face-to-face meetings and distance meetings are more effective than group meetings. Despite the existence of displacement effects, when we incorporate our results into an equilibrium search model we find that a complete roll-out of the program would lead to lower unemployment and reduced government spending.
Keywords: J68; J64; C93; 330; Vacancy referrals; Counseling; Job search; Randomized experiment